Capacitação de servidores públicos: avaliação do impacto do treinamento no trabalho - Farias, Litieli Tadiello Bedinoto (2025)
The National Policy for People Development (PNDP) guides the development process of federal public servants in Brazil. In the field of Training, Development, and Education (TD&E), there are methodologies and instruments aimed at evaluating development actions, with a view to the continuous improvement of this system. Accordingly, this study aims to assess the impact of training at work, with the goal of enhancing the People Development Plan (PDP) of a Public University. To achieve this objective, a descriptive research study was conducted using a quantitative approach, characterized as a survey with a cross-sectional design. The investigation combined multiple sources of information: the participants of the training programs (selfassessment), their immediate supervisors (hetero-assessment), and institutional documents (training reports and reaction evaluations to instructional procedures). The instrument applied to participants included a self-assessment scale measuring the impact of training on job performance (broad scope), a scale measuring support for training transfer, and questions regarding employee characteristics. For immediate supervisors, the instrument included a hetero-assessment scale of training impact (broad scope) and profile items. Data were collected through both online and printed questionnaires, resulting in a sample of 305 participants and 120 supervisors. The analyses included descriptive statistics, structural equation modeling using partial least squares (PLS-SEM), the non-parametric Mann-Whitney U test, and multigroup analysis (MGA). For the open-ended questions from reaction evaluations, content analysis was employed. The main findings indicate a high level of satisfaction among participants in the 2024 PDP courses, with particular emphasis on the instructors' performance and the practical contributions of the courses to professional tasks. A moderately positive perception was identified regarding support for training transfer to the workplace. The impact of training on job performance was also positively evaluated by both employees and supervisors, with the latter showing a slightly higher perception. In both assessments, the practical applicability of the courses stood out, reflecting improvements in the speed and quality of work activities. However, effects on more subjective aspects, such as motivation, were less noticeable. Furthermore, the study highlighted that peer support plays a fundamental role in applying new learning in the workplace. Material support also had a positive influence on training impact, whereas support from immediate supervisors did not show a statistically significant relationship. Finally, the results revealed that the leadership role held by the employee acts as a moderating variable in the relationship between material support and training application.